The sensitivity of CO and aerosol transport to the temporal and vertical distribution of North American boreal fire emissions - Chen, Y.; Li, Q.; Randerson, J. T; Lyons, E. A; Kahn, R. A; Nelson, D. L; Diner, D. J (Atmospheric Chemistry and Physics, 2009)
Forest fires in Alaska and western Canada represent important sources of aerosols and trace gases in North America. Among the largest uncertainties when modeling forest fire effects are the timing and injection height of biomass burning emissions. Here we simulate CO and aerosols over North America during the 2004 fire season, using the GEOS-Chem chemical transport model. We apply different temporal distributions and injection height profiles to the biomass burning emissions, and compare model results with satellite-, aircraft-, and ground-based measurements. We find that averaged over the fire season, the use of finer temporal resolved biomass burning emissions usually decreases CO and aerosol concentrations near the fire source region, and often enhances long-range transport. Among the individual temporal constraints, switching from monthly to 8-day time intervals for emissions has the largest effect on CO and aerosol distributions, and shows better agreement with measured day-to-day variability. Injection height substantially modifies the surface concentrations and vertical profiles of pollutants near the source region. Compared with CO, the simulation of black carbon aerosol is more sensitive to the temporal and injection height distribution of emissions. The use of MISR-derived injection heights improves agreement with surface aerosol measurements near the fire source. Our results indicate that the discrepancies between model simulations and MOPITT CO measurements near the Hudson Bay can not be attributed solely to the representation of injection height within the model. Frequent occurrence of strong convection in North America during summer tends to limit the influence of injection height parameterizations of fire emissions in Alaska and western Canada with respect to CO and aerosol distributions over eastern North America.